Human adenovirus type 4 (HAdV-4) associated acute respiratory tract infection in children & genetic characteristics of HAdV-4 in China: a prospective multicenter study - Wang, Jinjin; Feng, Qianyu; Duan, Yali; Ai, Junhong; Zhu, Yun; Wang, Ran; Chen, Xiangpeng; Lu, Gen; Sun, Yun; Li, Changchong; Jin, Rong; Shang, Yunxiao; et al. (BMC infectious diseases, 2024)
Human adenovirus (HAdV) is an important pathogen causing acute respiratory infection (ARI) in children. Many countries, including China, have experienced sporadic or outbreaks related to HAdV-4, and death cases were reported. However, there is little research on HAdV-4 and the epidemic situation of HAdV-4 in China is little known. This study was designed to comprehend the prevalence and genetic characteristics of HAdV-4 in ARI children in China. Respiratory tract samples from ARI children hospitalized in six hospitals of Northern and Southern China from 2017 to 2020 were collected for HAdV detection and typing. Clinical information was collected from HAdV-4 positive patients for clinical characteristics and epidemiological analysis. The main capsid proteins and the whole genome sequences were amplified and sequenced for bioinformatics analysis. There were 2847 ARI children enrolled, and 156 (5.48%) HAdV positive samples were detected. Eleven HAdV-4 positive samples were identified, accounting for 0.39% of the total samples and 7.05% of the HAdV positive samples. The main manifestations were fever and cough. Two children had conjunctivitis. Two children were diagnosed with severe pneumonia and developed respiratory failure. One of them developed hemophagocytic syndrome and checked in pediatric intensive care unit (PICU). This child had ventricular septal defect. All the children recovered. The isolated strains of HAdV-4 obtained in this study and the reference strains from China located in the same phylogenetic branch (HAdV-4a), while the prototype strain and vaccine strains formed another branch (HAdV-4p). Upon comparison with the prototype strain, there were a few amino acid mutations existing in three major capsid proteins. According to recombination analysis, no new recombination was found. The detection rate of HAdV-4 in children hospitalized with ARI was 0.39% in the total samples and 7.05% of all HAdV positive samples. HAdV-4 isolates obtained in this study and other reference strains from China belonged to the HAdV-4a subtype. Our data provided reference for the monitoring, prevention and control of HAdV-4, as well as the research and development of vaccines and drugs.